Building Information Modeling (BIM) integration in developing countries: An in-depth examination of adoption factors from public clients’ perspectives - Ozcan-Deniz, Gulbin; Ozorhon, Beliz; Kaya, Osman Can (International journal of architectural computing, 2025)
Over the past decade, the construction industry has undergone significant change due to technological advancements. Among these, Building Information Modeling (BIM) has been one of the pioneer technologies to impact this transformation. Projects using BIM reported increased productivity with expedited work of project stakeholders while maximizing their collaboration. While BIM has achieved remarkable success in developed countries, its adoption in developing countries remains limited. Studies showed that the acceptance of BIM technology is still very low in some countries. This study examines the status of BIM adoption including exploring the barriers as well as the factors that contribute to overcoming these barriers in adopting BIM in developing countries. BIM enablers in construction projects from the perspective of public clients were examined via a systematic review performed through the literature to identify these factors. Interviews were conducted with public clients to examine these factors. The average severity of each factor was ranked by clients. Notably, the study reveals that unfavorable economic conditions, high costs, and unclear project benefits as the significant barriers to BIM adoption. Clear advantages of BIM were reported as the ease of use, high analysis ability, positive attitude of the company, and demand/satisfaction of the clients.